ANALYSIS OF RISK FACTORS AND STROKE PREVENTION - Azmii, Nazhira; Susanti, Nofi; Syafira Irwani Siregar, Nazwa; Artila, Tita (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Stroke is a disease known as the “silent killer,” in which there is a loss of brain function caused by a loss of blood supply to the brain. Several factors can contribute to the occurrence of a stroke, which can be divided into modifiable factors and non-modifiable factors. Variables/modifiers include hypertension, smoking, diabetes mellitus (DM), heart disease, dyslipidemia, exercise and obesity, alcohol, drug abuse, oral contraceptives, blood disorders, sleep, lipoproteins and homocysteine . On the other hand, factors that cannot be changed are age, gender, race/ethnicity, and genetics. The purpose of this study was to determine the repeated risk factors and prevention of repeated strokes. The method used in this study is research and literature research, and the source is obtained from Proquest, Ovid, and Google Schoolar. 20 scientific journals were used in this study. The results showed that the main risk factors causing a stroke are the accumulation of fatty substances, cholesterol, calcium and other elements that supply blood to the heart and brain muscles, which has the effect of reducing the blood flow to the brain and heart. But strokes can be prevented by several efforts, stroke prevention efforts are carried out through several programs, one of which is the effect of providing healthy lifestyles CERDIK andPATUH Prevent stroke modification to stroke sufferers so that they know the promotive efforts of prevention of stroke.